PRINCIPLES OF PREVENTION AND TREATMENT OF CARIES ON THE APROXIMAL SURFACES OF TEETH IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Caries of the approximal surfaces of teeth is not only highly common nowadays, but also gives the most frequent complications — the main cause of pulpitis and periodontitis. It is the most difficult to diagnose and the most difficult to treat. Therefore, its timely prevention and effective treatment are one of the most important tasks of modern dentistry. The absence of symptoms of secondary caries in the early stages of its occurrence, especially on the approximal surfaces of teeth, creates the impression of a successful therapeutic treatment, but repeated cycles of excision of necrotic tissues followed by filling weaken the crown of the tooth so much that later this leads to its removal. Currently, addressing the problem of dental caries in scientific research does not seem promising for many, since hundreds of applied and fundamental works of the last century and several years of the XXI century are devoted to this. At the same time, epidemiological studies conducted in Uzbekistan show that the prevalence and intensity of dental caries in the population are not decreasing. And the number of recurrences of the carious process and cases of secondary caries development significantly exceeds that in the developed countries of Europe and America. It is in connection with secondary and recurrent caries that about 40% of all therapeutic dental measures related to dental treatment are carried out. This consumes a third of the dentist's working time. Modern developments of filling materials and dental restoration techniques are aimed at preventing secondary and recurrent caries.